Evidence that bank vole PrP is a universal acceptor for prions. - Joel C Watts; Kurt Giles; Smita Patel; Abby Oehler; Stephen J DeArmond; Stanley B Prusiner (PLoS Pathogens)
Bank voles are uniquely susceptible to a wide range of prion strains isolated from many different species. To determine if this enhanced susceptibility to interspecies prion transmission is encoded within the sequence of the bank vole prion protein (BVPrP), we inoculated Tg(M109) and Tg(I109) mice, which express BVPrP containing either methionine or isoleucine at polymorphic codon 109, with 16 prion isolates from 8 different species: humans, cattle, elk, sheep, guinea pigs, hamsters, mice, and meadow voles. Efficient disease transmission was observed in both Tg(M109) and Tg(I109) mice. For instance, inoculation of the most common human prion strain, sporadic Creutzfeldt-Jakob disease (sCJD) subtype MM1, into Tg(M109) mice gave incubation periods of ∼200 days that were shortened slightly on second passage. Chronic wasting disease prions exhibited an incubation time of ∼250 days, which shortened to ∼150 days upon second passage in Tg(M109) mice. Unexpectedly, bovine spongiform encephalopathy and variant CJD prions caused rapid neurological dysfunction in Tg(M109) mice upon second passage, with incubation periods of 64 and 40 days, respectively. Despite the rapid incubation periods, other strain-specified properties of many prion isolates--including the size of proteinase K-resistant PrPSc, the pattern of cerebral PrPSc deposition, and the conformational stability--were remarkably conserved upon serial passage in Tg(M109) mice. Our results demonstrate that expression of BVPrP is sufficient to engender enhanced susceptibility to a diverse range of prion isolates, suggesting that BVPrP may be a universal acceptor for prions.